Derivational morphonology of the substantive new words in Ukrainian and Russian languages (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The article analyzes the new words of modern Ukrainian and Russian, the productive morfonological phenomena of the new words are found, the specific features and patterns of their creation are compared in modern Ukrainian and Russian languages.
Keywords: noun derivatives; morfonological phenomena; phoneme alternations; change of accentuation